Peripheral vasculopathy in Raynaud phenomenon: Vascular disease biomarkers - Silva,Ivone (2016)
Background: Introduction: Raynaud's phenomenon (RP) is a well-deﬁned clinical syndrome. Systemic sclerosis (SSc) is the most frequent associated disease to RP (96%). The aim of this study was to assess the differences between primary RP (PRP) and secondary RP (SRP) regarding macrovascular disease parameters, endothelial dysfunction and angiogenesis biomarkers. Materials and methods: Flow-mediated dilatation (FMD), endothelin-1 (ET-1), asymmetric dimethylarginine (ADMA) vascular endothelial growth factor (VEGF), endoglin and endostatin were analyzed in a cohort study of 32 PRP patients and 77 SRP all with SSc. 38 of the SRP SSc-associated patients had severe digital ulcer (DU). Results: Patients with PRP had signiﬁcantly longer history of RP compared to SRP SSc-sssociated patients (p = 0.028). FMD was signiﬁcantly lower in SRP patients 10.85 ± 11.0% (p < 0.001), more evidenced in SRP SSc-associated DU patients 5.34 ± 7.49 (p < 0.001). ET-1 plasma levels were signiﬁcantly increased in both PRP 7.53 (0.16--11.73) and SRP patients 11.85 (7.42--17.23) (p < 0.001). Signiﬁcant increased serum levels of ADMA 0.52 (0.45--0.63) µmol/L (p < 0.001) and endoglin 3.01 (1.46--7.02) mg/ml (p < 0.001) were found in the SRP SSc-associated group with DU. VEGF was signiﬁcantly decreased in the DU group 245.06 (158.68--347.33) pg/ml compared to PRP 438.50 (269.26-854.00) pg/ml and SRP naïve-DU patients 290 (166.71--361.78) pg/ml patients (p < 0.001). No signiﬁcant differences were found between groups regarding endostatin (p = 0.118). Comparing PRP and SRP SSc-associated patients without DU no statistically signiﬁcant difference regarding FMD, ET-1, ADMA, VEGF, plasma levels were observed. Conclusion: Overproduction of ET-1 and VEGF is present in PRP patients. Macrovascular disease and an impaired response to shear stress are more characteristic of SRP with a grater expression in patients with peripheral ischemic lesions.